Support needs and adaptive behavior surveys: Services prediction and relationship - Annalisa V. Piccorelli; Eric J. Moody; David Heath; Ethan Dahl; Sandy Root-Elledge (PLoS ONE, 2025)
The Inventory for Client and Agency Planning (ICAP) and the Supports Intensity Scale (SIS) have been used to determine Medicaid eligibility for individuals with disabilities but are designed to capture different information. This project explored how these surveys relate to services received and each other. ICAP and SIS surveys were conducted on 125 Wyoming adults with intellectual and developmental disabilities eligible for a Medicaid Waiver. Results suggest that both measures were strongly associated and could be used to predict services. However, this study suggests that the SIS and ICAP summary measures were separate constructs. Therefore, both instruments can be used to determine Medicaid eligibility, but implementers should be aware of differences in the types of constructs being captured.